The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1002/ejoc.200900742
|View full text |Cite
|
Sign up to set email alerts
|

Concise Synthesis of (±)‐Aurantioclavine through a Base‐Promoted Pictet–Spengler Reaction

Abstract: A concise total synthesis of (±)‐aurantioclavine (1) was completed in three steps through the base‐promoted Pictet–Spengler reaction of Nb‐benzylserotonin with 3‐methylbut‐2‐enal. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2009)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…only three steps from N b -benzyl-serotonine and alkylaldehydes by using this strategy. 7 Recently, we reported the first synthesis of the azepinoindole alkaloid hyrtioreticulins C and D through a base-promoted C-4 Pictet-Spengler reaction between tryptophan and acetaldehyde. 8 Although these results demonstrated that such a biomimetic cascade toward hyrtiazepines was possible, there were a few challenges in the synthesis of these alkaloids.…”
Section: Special Topic Syn Thesismentioning
confidence: 99%
“…only three steps from N b -benzyl-serotonine and alkylaldehydes by using this strategy. 7 Recently, we reported the first synthesis of the azepinoindole alkaloid hyrtioreticulins C and D through a base-promoted C-4 Pictet-Spengler reaction between tryptophan and acetaldehyde. 8 Although these results demonstrated that such a biomimetic cascade toward hyrtiazepines was possible, there were a few challenges in the synthesis of these alkaloids.…”
Section: Special Topic Syn Thesismentioning
confidence: 99%
“…27 Completed in just 3 linear steps and 21% overall yield from readily accessible starting materials, it represents the shortest total synthesis to date. The authors anticipated that the natural product could be obtained from the pivotal 5-hydroxy indole derivative 39 , which should be well-suited for further deoxygenation (Figure 5).…”
Section: Synthetic Approaches To Rearranged Clavine Alkaloids Covementioning
confidence: 99%
“…Interestingly, the structures of Friedel-Crafts products 38–40 map closely onto the clavicipitic 28 and aurantioclavine 29 ergot alkaloids (Figure 2), where the unusual C–C bond between the indole and the isoprene unit is biosynthetically constructed through a Friedel-Crafts alkylation of tryptophan onto dimethylallyl diphosphate. 28,30 …”
Section: Cyclization Of Bisindoles 34 and 35mentioning
confidence: 99%